Bioequivalence Study of Rofecoxib Tablets - Koytchev, Rossen; Ozalp, Yildiz; Erenmemisoglu, Aydin; Meer, Mike John van der; Alpan, Recep Serdar (Arzneimittelforschung, 2004)
The study was designed to evaluate the bioavailability of two rofecoxib (CAS 162011-90-7) tablet formulations. Twenty-four healthy male volunteers were administered a 25 mg tablet of the test formulation (Ecrox®) containing rofecoxib or the originator product (reference). The trial was performed according to an open, cross-over design with a wash-out period of 7 days. Blood samples were taken up to 72 h post dose, the plasma was separated and the concentrations of rofecoxib were determined by an HPLC method. The mean Cmax were 192.07 ng/mL and 187.35 ng/mL, while the mean AUC0–t were 3613.84 ng · h/mL and 3501.56 ng · h/mL for the test and reference formulations, respectively. The median tmax was 3.75 h for the test tablet and 4.00 h for the reference formulation. The mean t1/2 el was 10.66 h and 10.61 h for the test and reference formulation, respectively. Mean MRT values for the test and reference tablets were 15.34 h and 15.33 h, respectively. No significant differences of pharmacokinetic parameters between the two studied formulations were found. The 90 % confidence interval for the primary target parameters, i.e. intra-individual ratios of AUC0–t and Cmax of rofecoxib were between 0.99 and 1.10 (AUC0–t) as well as between 0.96 and 1.10 (Cmax) and thus within the acceptance ranges. Concerning the secondary parameter tmax the 90 % confidence interval for the intra-individual differences was between -0.25 and 0.25 h. In the light of the present study it can be concluded that the two evaluated rofecoxib formulations, i.e. test tablets of rofecoxib and a reference preparation are bioequivalent in terms of the rate and extent of absorption.
Keywords: CAS 162011-90-7; Ecrox®; Rofecoxib, bioequivalence, clinical pharmacokinetics